2009
DOI: 10.1194/jlr.r800024-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of PAF acetylhydrolase

Abstract: Platelet-activating factor (PAF), a phospholipid autacoid with potent effects throughout the innate immune system, is selectively degraded by two small families of PAF acetylhydrolases (PAF-AHs). These Ca 21 -independent phospholipases A 2 display remarkable specificity for the length of the sn -2 residue, but this selectivity is lost as the residue gains oxygen functions. Two of the PAF-AHs therefore are specific oxidized phospholipid phospholipases that reduce inflammation, but also remove oxidatively trunca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 51 publications
2
119
0
12
Order By: Relevance
“…The local expression of PAF-AH in arteries of non-hyperlipidemic rabbits reduced the accumulation of oxidatively modified LDL without changing plasma levels of PAF-AH and reduced the expression of endothelial cell adhesion molecules (Arakawa et al 2005). PAF-AH deficiency caused by a missense mutation in the gene has been indicated to be an independent risk factor for CAD in Japanese men (McIntyre et al 2009). In contrast to this both activity and mass concentration of LpPLA2 in total serum has been associated with increased rather than decreased cardiovascular risk (Lp et al 2010).…”
Section: Mechanisms Under Physiological Conditionsmentioning
confidence: 99%
“…The local expression of PAF-AH in arteries of non-hyperlipidemic rabbits reduced the accumulation of oxidatively modified LDL without changing plasma levels of PAF-AH and reduced the expression of endothelial cell adhesion molecules (Arakawa et al 2005). PAF-AH deficiency caused by a missense mutation in the gene has been indicated to be an independent risk factor for CAD in Japanese men (McIntyre et al 2009). In contrast to this both activity and mass concentration of LpPLA2 in total serum has been associated with increased rather than decreased cardiovascular risk (Lp et al 2010).…”
Section: Mechanisms Under Physiological Conditionsmentioning
confidence: 99%
“…PAF-AH is synthesised throughout the brain, white adipose tissue and placenta. Macrophages represent the most important source of the circulating enzyme (McIntyre et al 2009). Plasma PAF-AH circulates in association with LDL and HDL particles, with the majority of the enzyme bound to small, dense LDL and to lipoprotein (a) (Tselepis et al 1995).…”
Section: Enzymesmentioning
confidence: 99%
“…(Table 3) The logistic regression test revealed that older age ( ≄ 65 years old), diabetes mellitus (DM), a positive past history of significant coronary artery obstruction treated by percutaneous coronary intervention (PCI) and the presence of significant ECCA stenosis were strongly associated with elevated Lp-PLA2 mRNA expression of PBMNCs. factor which may promote the generation of oxidized LDL-C and free fatty acid with subsequent direct participation in the formation and rupture of carotid plaques 10,12,15,18,19) . Our results also revealed a strong association between significant coronary artery or ECCA stenosis and elevated Lp-PLA2 mRNA expression of PBMNCs.…”
Section: Comparison Of Baseline Characteristics Between Patients Withmentioning
confidence: 99%
“…Of these biomarkers [1][2][3][4][5][6][7][8][9][10] , lipoprotein-associated phospholipase A2 (Lp-PLA2) has recently been described as a novel biomarker which is strongly associated with atherosclerosis-related inflammatory processes and plaque instability in histopathologic studies of the coronary and carotid arteries [10][11][12] . Lp-PLA2, also known as platelet-activating factor acetylhydrolase, is produced predominantly by monocyte-derived macrophages, T-lymphocytes and mast cells [13][14][15] . Many studies have demonstrated that Lp-PLA2 is an enzyme with broad capabilities, allowing cleavage of oxidized fatty acids at the sn-2 position of oxidized phospholipids and the generation of lysophosphatidylcholine, free oxidized fatty acids and bioactive proatherogenic lipids 10,16) .…”
Section: Protocol For Rna Extractionmentioning
confidence: 99%